Physical education, language and the social function of the school - Portela, Thalita Regina de Oliveira (2023)
This article discuss the insertion of Physical Education as a curricular component belonging to the area of Languages, Codes and its Technologies, with the objective of advancing in the understanding of a perspective that justifies this belonging to this area and how this fact allows the approximation of the component curriculum with the Social Function of the School, with citizen training and with the understanding of differences. It argues that language, through its systems of meaning, acts as a regulatory agent and producer of bodies and identities, directly affecting the pedagogical treatment destined to the contents of Physical Education in Basic Education, which must have as its object of study the body culture. Finally, it emphasizes that this understanding of the curricular component allows its integration into the social function of the School.